Explaining the experience of telephone cardiopulmonary resuscitation in Kermanshah emergency medical dispatch: A qualitative, phenomenological study - Fatemeh Zaheri; Alireza Abdi; Mahmoud Rahmati (BMC Emergency Medicine)
Abstract Background Telephone Cardiopulmonary Resuscitation (T-CPR), administered by Emergency Medical Dispatchers (EMDs) to bystanders at the scene of an out-of-hospital cardiac arrest (OHCA), faces significant challenges. These challenges arise when collaboration for CPR is difficult due to the bystander’s condition or when the patient’s condition is not visible. Limited research exists on T-CPR, which is why our study aims to explore the experiences of Kermanshah EMDs in providing T-CPR. Method This descriptive phenomenological (because there is lack of information and study about this subject in Iran and importance of a deep understanding to examine different aspect of the subject) study was conducted with 12 EMDs from a total of 20 in Kermanshah EMDs. Data were collected through in-depth, semi-structured interviews with participants selected via purposive sampling. The study was qualitative and the questionnaire was not validated. Interviews consisted of both open-ended and probing questions. This research was carried out in 2020–2021. Data were analyzed thematically using Collizi’s seven-step. Result Analysis of the 12 interviews conducted with dispatchers who had an average age of 28.33 years and 2.33 years of work experience resulted in the identification of 456 codes. These codes were categorized into three main themes: (1) “Perceived Nursing Care in T-CPR,” which includes sub-themes such as Ethical and Emotional Management in Care, Empathetic Care, Crisis Management and Stress Control; (2) “Professional Abilities of EMDs,” which includes sub-themes like Perceived Professional Skills and Satisfaction from Successful Performance; and (3) “Cultural Necessities Related to Telephone Resuscitation,” with sub-themes such as Challenges of Training, Communication Barriers and the Need for Public Education and Cultural Change. Conclusion Participants reported that T-CPR is often unsuccessful due to factors such as non-collaboration from bystanders or improper execution, stemming from low education levels, cultural barriers and a general lack of public awareness about emergency procedures. Successful T-CPR requires dispatchers to skillfully communicate with anxious bystanders and correct misconceptions that CPR may worsen the patient’s condition. Additionally, fluency in various accents, improving public education, and implementing effective stress management strategies are essential for improving outcomes. Addressing these issues through better education and cultural change is vital for enhancing T-CPR effectiveness.